PENGARUH ANGKA HARAPAN LAMA SEKOLAH, RATA-RATA LAMA SEKOLAH, DAN PENGELUARAN PER KAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA - Mahya, A. Jauhar; Widowati, Widowati (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2021)
The Human Development Index (HDI) is data and information used by local governments to measure the achievement of human development with a number of basic components of quality of life. HDI is formed by three basic dimensions, a long and healthy life which is described by the life expectancy of newborns, knowledge which is described by the average length of schooling and expected length of schooling, and a decent standard of living as described by per capita expenditures are adjusted accordingly.The purpose of this study is to explain whether there is an influence, and to obtain a large number of effects from the expected length of schooling, average length of schooling, and per capita expenditure together with the Human Develpoment Index in Central Java Province. This study was completed using multiple linear regression analysis with the help of SPSS 1.6 (Statistical Package for Social Sciences) software. The results of this study show that the expected length of schooling, average length of schooling, and per capita expenditure have a significant effect on the human development index, which is 97.8% and only 2.2% is influenced by other factors.